2014
DOI: 10.3349/ymj.2014.55.4.937
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Cost-Effectiveness of Bridge Therapies for Invasive Dental Procedures in Patients with Mechanical Heart Valves

Abstract: PurposeBridge anticoagulation therapy is mostly utilized in patients with mechanical heart valves (MHV) receiving warfarin therapy during invasive dental procedures because of the risk of excessive bleeding related to highly vascular supporting dental structures. Bridge therapy using low molecular weight heparin may be an attractive option for invasive dental procedures; however, its safety and cost-effectiveness compared with unfractionated heparin (UFH) is uncertain.Materials and MethodsThis study investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 21 publications
(26 reference statements)
1
12
0
Order By: Relevance
“…15 A prospective cohort of patients with MHV who had a dental procedure in the setting of bridge therapy identified a 30-day bleeding rate of 5.4% with 1 TE complication (0.6%). 16 Unfortunately, outcomes in patients not receiving bridge therapy were not assessed. 16 Daniels and colleagues performed a cohort study of patients with MHV who had an invasive procedure with or without bridge therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 A prospective cohort of patients with MHV who had a dental procedure in the setting of bridge therapy identified a 30-day bleeding rate of 5.4% with 1 TE complication (0.6%). 16 Unfortunately, outcomes in patients not receiving bridge therapy were not assessed. 16 Daniels and colleagues performed a cohort study of patients with MHV who had an invasive procedure with or without bridge therapy.…”
Section: Discussionmentioning
confidence: 99%
“…16 Unfortunately, outcomes in patients not receiving bridge therapy were not assessed. 16 Daniels and colleagues performed a cohort study of patients with MHV who had an invasive procedure with or without bridge therapy. 17 Similar to our study, the rates of TE were very low and equivalent in the bridged and unbridged groups, while major bleeding was numerically greater in the setting of bridge therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The average age of the participants ranged from 57 to 67 years, and the participants were predominantly men. The studies included more aortic MHVs, except for the study by Won et al (2014). The risk factors for TEs reported by each study were heart failure, diabetes mellitus, history of thrombosis, atrial fibrillation (AF), and previous stroke or TIA.…”
Section: Sample Populationsmentioning
confidence: 99%
“…The study by Hart et al (2017) only reported specific procedures in relation to complications, but did not provide an all-inclusive list of procedures. Won et al (2014) only studied participants who underwent dental procedures with a moderate or high risk of bleeding. The other three studies listed and categorized similar high risk of bleeding invasive procedures or surgeries by specialty such as orthopedic, cardiothoracic, interventional radiology, general surgery, ophthalmologic, gynecological, vascular, and procedures of the ear, nose, and throat.…”
Section: Sample Populationsmentioning
confidence: 99%
See 1 more Smart Citation